2005
DOI: 10.1027/0227-5910.26.3.104
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Developing Countries (1)

Abstract: Epidemiological investigations of this kind have the potential to inform suicide prevention efforts in developing countries, and should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(39 citation statements)
references
References 15 publications
4
32
0
3
Order By: Relevance
“…To the best of our knowledge, this is the first trial from a low- and middle-income country demonstrating the impact of interventions for a mental disorder on suicidal behaviours, a major public health priority in these countries. 26 The apparently larger absolute effects of the intervention in the short-term are in line with other trials for the treatment of common mental disorders, …”
Section: Discussionsupporting
confidence: 79%
“…To the best of our knowledge, this is the first trial from a low- and middle-income country demonstrating the impact of interventions for a mental disorder on suicidal behaviours, a major public health priority in these countries. 26 The apparently larger absolute effects of the intervention in the short-term are in line with other trials for the treatment of common mental disorders, …”
Section: Discussionsupporting
confidence: 79%
“…This also corresponds well with Durkheim's theory (19). Higher education has been associated with a high risk of suicide in several other studies (29,30). …”
Section: Discussionmentioning
confidence: 74%
“…[1] The actual number of suicides is understandably more than the reported official figures as non-reporting, under-reporting, and misclassification are prevalent due to various socio-cultural stigmas, religious sanctions, legal issues, and insufficient registration systems. [2] It has been suggested that the annual suicide rate could be six to nine times the official rate. [1] There has been less work in systematic profiling of risk factors in developing countries compared to the developed counterparts.…”
Section: Introductionmentioning
confidence: 99%